2019
DOI: 10.1002/open.201900203
|View full text |Cite
|
Sign up to set email alerts
|

Heterolepic β‐Ketoiminate Zinc Phenoxide Complexes as Efficient Catalysts for the Ring Opening Polymerization of Lactide

Abstract: Zinc phenoxide complexes L 1 ZnOAr 1 – 4 (L 1 =Me 2 NC 2 H 4 NC(Me)CHC(Me)O) and L 2 ZnOAr 5 – 8 (L 2 =Me 2 NC 3 H 6 NC(Me)CHC(Me)O) with donor‐functionalized β ‐ketoimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 117 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…Complexes 3 and 5 , which contain two electron-donating (+I effect) tert -butyl groups in both ortho positions of the phenoxide ligand, showed far better activities than those of complexes 4 and 6 . Similar findings on the beneficial role of electron-donating groups at the phenoxide moiety for the ROP of cyclic esters were previously reported. , This phenomenon can be explained by the enhanced nucleophilicity of the phenoxide oxygen atom in complexes 3 and 5 ; according to that, the nucleophilic attack at the electrophilic carbonyl moiety of the coordinated lactide becomes more favorable. In addition, the higher steric demand of the ortho tert -butyl groups in complexes 3 and 5 furthermore favors the alkoxide dissociation due to steric repulsion, also resulting in a higher catalytic activity.…”
Section: Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Complexes 3 and 5 , which contain two electron-donating (+I effect) tert -butyl groups in both ortho positions of the phenoxide ligand, showed far better activities than those of complexes 4 and 6 . Similar findings on the beneficial role of electron-donating groups at the phenoxide moiety for the ROP of cyclic esters were previously reported. , This phenomenon can be explained by the enhanced nucleophilicity of the phenoxide oxygen atom in complexes 3 and 5 ; according to that, the nucleophilic attack at the electrophilic carbonyl moiety of the coordinated lactide becomes more favorable. In addition, the higher steric demand of the ortho tert -butyl groups in complexes 3 and 5 furthermore favors the alkoxide dissociation due to steric repulsion, also resulting in a higher catalytic activity.…”
Section: Results and Discussionsupporting
confidence: 85%
“…However, the different structures of complexes 3 and 5 versus those of complexes 4 and 6 clearly result from the presence of sterically demanding ortho tert -butyl substituents of the phenoxide groups in complexes 3 and 5 ; hence, the steric demand of the alkoxide ligand is responsible for the catalytic activity. The analysis of the resulting TOF values also revealed that the L 2 -substituted phenoxide complexes ( 5 and 6 ) containing the C 3 -spacer are slightly more active than the corresponding L 1 -substituted phenoxide complexes ( 3 and 4 ) containing the C 2 -spacer as was previously reported. , …”
Section: Results and Discussionsupporting
confidence: 80%
“…Complexes 1 and 2 were purified by re‐crystallization from saturated solutions in toluene at −30 °C (Scheme 2). Since heteroleptic zinc alkoxide complexes typically show enhanced catalytic activities in the ROP of lactones compared to the corresponding zinc alkyl complexes, [5b] we reacted LZnEt 2 with one equivalent of phenol ArOH (Ar=2,6‐Me 2 −C 6 H 3 ) in toluene. However, after crystallization from a saturated solution in THF at 0 °C, the homoleptic thf‐coordinated complex L 2 Zn(thf) 2 3 (Scheme 2) was obtained as was proven by 1 H NMR spectroscopy and single crystal X‐ray diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…The Li–O bond lengths range from 1.851(3) Å to 2.144(3) Å and the Li–N bond lengths from 2.065(3) Å to 2.287(3) Å. The formation of trinuclear complexes has been reported for the donor‐functionalized β ‐ketoiminate lithium complex [LiOC(CH 3 )CHC(CH 3 )N(H)CH 2 CH 2 N(CH 3 ) 2 ] 3 ,[19c] which shows slightly elongated Li–O and Li–N bonds. In contrast, dinuclear and tetranuclear lithium β ‐ketoiminate complexes show similar Li–O and Li–N bond lengths compared to 1 and 5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our interest in complexes containing β ‐diketiminate and β ‐ketoiminate substituents including donor‐functionalized ligands prompted our interest toward perfluorinated β ‐diketiminate ligands . We now extend these studies on partly fluorinated donor‐functionalized β ‐ketoiminate ligands and report on the synthesis and structures of six alkali metal complexes and one platinum complex, which was shown to be a suitable CVD precursor for the deposition of crystalline Pt films.…”
Section: Introductionmentioning
confidence: 99%